2007
DOI: 10.1111/j.1748-1716.2007.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dual endothelin receptor antagonist tezosentan and hypertonic saline/dextran on porcine endotoxin shock

Abstract: Tezosentan, alone and in combination with HSD, improved cardiac index and arterial oxygenation. The addition of HSD to tezosentan treatment did not improve the endotoxin-induced hypotension, but beneficial effects on microcirculation and systemic oxygenation were seen despite low perfusion pressure, as indicated by increased SvO(2) and reduced metabolic acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Infusion of HSS to the calves of group B also decreased the pressure of CO 2 resulting in increased blood pH and bicarbonates which helped in recovering the calves from acidosis. These results are supported by the findings of several previous studies (Constable et al, 1991b;Senturk, 2003;Somell et al, 2007;Koch and Kaske, 2008;Hasanpour et al, 2009;Leal et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Infusion of HSS to the calves of group B also decreased the pressure of CO 2 resulting in increased blood pH and bicarbonates which helped in recovering the calves from acidosis. These results are supported by the findings of several previous studies (Constable et al, 1991b;Senturk, 2003;Somell et al, 2007;Koch and Kaske, 2008;Hasanpour et al, 2009;Leal et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Hypertonic saline solution caused immediate and significant increase in MAP and CVP values which had fallen in calves as a consequence of neonatal diarrhea. This is most likely a volume resuscitation effect associated with increased preload and inherent positive inotropic effect of HSS (Somell et al, 2007). The other factor involved is the rapid plasma volume expansion, which occurs within 1 h of the infusion because of the immediate increase in serum osmolarity and serum sodium concentration, promoting fluid circumvent from intracellular compartment and gastrointestinal tract (Constable et al, 1991b;Rocha e Silva, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tezosentan is approximately 30-fold more potent on ET A than on ET B receptors [14]. Recently tezosentan has been shown to improve hemodynamics [15,16], pulmonary function [17,18], and renal function [19] in endotoxemic shock. However, to the best of our knowledge the effects of tezosentan on splanchnic microcirculation in sepsis or endotoxemia have thus far not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…56 In a rat model of endotoxin administration, Yu et al 41 report that small volume resuscitation with hypertonic saline or hypertonic sodium chloride + hydroxyethyl starch 40 reduced lung damage when compared to isotonic saline. In a porcine model of endotoxemic sepsis, Somell et al 57 claim that the combination of tezosentan and hypertonic saline-dextran improved cardiac index and arterial oxygenation. In a two hit model (hemorrhage + cecal ligation puncture), Kim et al 58 showed that the combination of hypertonic saline and pentoxifylline when compared to lactated Ringers reduced lung injury score and neutrophil count.…”
Section: Superioritymentioning
confidence: 99%